THE POLICY OF GRANTING REMISSION TO CORRUPTION INMATES IN ORDER TO ERADICATE CORRUPTION IN INDONESIA - M Ali Zaidan (Jurnal Dinamika Hukum, 2016)
Corruption is an extraordinary crime, even though the laws have been revised and has a more progressive character has also established Anti-Corruption Commission the number of crimes of corruption still do not show any significant change. In the midst of public pessimism, the Ministry of Justice and Human Rights has initiated efforts to revise the Government Regulation Number 99 Year 2012. The tightening of remission meant that the convict is not easy to get their sentences reduced. Attempts to revise the provisions concerning remission, it should consider how far can reduce corruption and its impact on inmates and the public.Key words: extraordinary crime,corruption, remission.